Stereotip Antara Penduduk Asli dan Pendatang di Kota Sorong – Papua Barat Daya - Abduh, Ichsan Muhammad; Hasrullah , Hasrullah; Cangara, Hafied; Pulubuhu, Dwia Aries Tina (Jurnal Audiens, 2025)
This study aims to describe the perspectives/stereotypes towards each other between the indigenous and immigrant populations in the Sorong City area. The indigenous Papuan population is defined as the population that falls into 3 criteria, namely those whose father/mother is of indigenous Papuan descent, or one of whose parents is of Papuan descent, and people who have been traditionally adopted as indigenous Papuans, while the immigrant population group is a non-Papuan population that comes from all over the Indonesian archipelago. The research used a qualitative method by interviewing 5 informants from each group. The results showed that both groups collectively claimed themselves to be part of the Papuan community. The indigenous people view the newcomers based on two criteria: ethnic status and their role in contributing to the Papuan community in Sorong City. Ethnically, newcomers are those who do not have Papuan bloodlines from either or both parents, resulting in the label of "newcomer" that continues to stick. In terms of "role," they are seen as having made significant contributions to the progress of Sorong City in areas like knowledge, expertise, and decision-making principles. Meanwhile, the newcomers perceive the indigenous people based on human resource (HR) quality and personality factors. Regarding HR quality, there is still a considerable gap between the indigenous people and the newcomers, especially in educational attainment, which affects various aspects of indigenous people's quality, including economic, social, and governmental domains. In terms of "personality," newcomers consider the indigenous people to have admirable qualities, particularly their strong sense of loyalty and reciprocity. Certain perspectives that lead to conflicts are mainly driven by personal or group interests, which often associate ethnic status as a trigger for differences.